Relationship Between Knowledge And Peers With Sexual Behavior Among Adolescents At SMAN 10 Kota Bengkulu In 2025 - Ahtiyah Salwa; Desi Aulia Umami; Indra Iswari (Universitas Dehasen Bengkulu, 2026)
Adolescents are highly susceptible to environmental influences, particularly those related to sexual behavior. Limited knowledge of reproductive health and strong peer pressure are among the major factors contributing to premarital sexual behavior. This study aimed to assess the relationship between knowledge and peer influence with premarital sexual behavior among adolescents at SMAN 10 Bengkulu City in 2025.Methods: A quantitative analytic study with a cross-sectional design was conducted. The sample consisted of 152 eleventh-grade students selected through purposive sampling from a population of 242 students. Data were collected using a structured and validated questionnaire and analyzed using the chi-square test. Results: The findings revealed that 66.4% of respondents had good knowledge about the risks of premarital sex, and 80.9% reported low levels of peer influence. A total of 76.3% demonstrated positive sexual behavior by avoiding premarital sex. Statistical analysis showed a significant association between knowledge and premarital sexual behavior (p = 0.021), whereas peer influence was not significantly associated (p = 0.228). Conclusion: Adolescent knowledge about reproductive health significantly contributes to safer sexual behavior, whereas peer influence was not a determining factor in this study. It is recommended that schools enhance reproductive health education through regular counseling programs, and that parents engage in open discussions regarding sexual health. Further research is encouraged to examine other factors such as digital media exposure and parenting styles.